Iron partitioning at a single station north of South Georgia during POLARSTERN cruise ANT-XXVIII/3 - Luis Miguel Laglera; Juan Santos-Echeandía; Lisa Fischer; Stephan Hann (PANGAEA, 2025)
In order to infer the effect of the strong dominant winds in the north of South Georgia, we collected unfiltered and filtered by 0.2 and 53 μm samples in the upper 300 m of the water column during the Polarstern cruise ANT-XXVIII/3. Iron concentrations were determined onboard by voltammetry after at least 24 h acidification at pH 2.0 and addition of 2,3 dihydroxynaphtalene (Laglera et al. Analytical Chemistry, 2013). We also applied an acidification leaching protocol to the unfiltered and filtered samples to study the evolution of iron release from sinking particles.